The upper thermal limit of epaulette sharks (Hemiscyllium ocellatum) is conserved across three life history stages, sex and body size. Issue 1 (28th December 2022) - Wheeler, Carolyn R; Lang, Bethan J; Mandelman, John W; Rummer, Jodie L
Abstract: Owing to climate change, most notably the increasing frequency of marine heatwaves and long-term ocean warming, better elucidating the upper thermal limits of marine fishes is important for predicting the future of species and populations. The critical thermal maximum (CTmax ), or the highest temperature a species can tolerate, is a physiological metric that is used to establish upper thermal limits. Among marine organisms, this metric is commonly assessed in bony fishes but less so in other taxonomic groups, such as elasmobranchs (subclass of sharks, rays and skates), where only thermal acclimation effects on CTmax have been assessed. Herein, we tested whether three life history stages, sex and body size affected CTmax in a tropical elasmobranch, the epaulette shark ( Hemiscyllium ocellatum ), collected from the reef flats surrounding Heron Island, Australia. Overall, we found no difference in CTmax between life history stages, sexes or across a range of body sizes. Findings from this research suggest that the energetically costly processes (i.e. growth, maturation and reproduction) associated with the life history stages occupying these tropical reef flats do not change overall acute thermal tolerance. However, it is important to note that neither embryos developing in ovo, neonates, nor females actively encapsulating egg cases were observed in or collected from the reef flats. Overall, our findings provide the first evidence in an elasmobranch that upper thermal tolerance is not impacted by life history stage or size. This information will help to improve our understanding of how anthropogenic climate change may (or may not) disproportionally affect particular life stages and, as such, where additional conservation and management actions may be required.